Pengaruh Proporsi Jumlah Tanaman Dalam Sistem Tanam Tumpangsari Kubis Bunga (Brassica oleracea L var. PM 126) dan Kedelai (Glycine max var. Anjasmoro) Terhadap Produksi Tanaman di Lahan Sawah - Nurhasyifa, Nurhasyifa; Supriadi, Devie Rienzani; Sugiono, Darso; Azizah, Elia (JURNAL AGROPLASMA, 2023)
Intercropping system is closely related to the planting of different plant commodities at the same time and land, so it is not surprising if it creates positive or negative interactions between plants. Thus, efforts to regulate the proportion of plants in intercropping are important to be considered. The aim of study to obtain the best intercropping proportions in cauliflower and soybean crops. The research was conducted on Bintang Alam land, Telukjambe Timur, Karawang District in December 2022 - March 2023. The research was used experiment method with Randomized Block Design (RBD) single factor with 5 treatments of intercropping proportions repeated 5 times. The treatments given were; K1 = 100% cauliflower, K2 = 25% cauliflower + 75% soybean, K3 = 50% cauliflower + 50% soybean, K4 = 75% cauliflower + 25% soybean, K5 = 100% soybean. The results were analyzed with the F test at the rate of 5% and further tested with the Least Significant Difference (LSD) at the rate of 5%. The best intercropping system proportion was K3 treatment (50% cauliflower + 50% soybean), with the largest LER value of 1.49 and a balanced ratio of crop CR values of 0.72 (cauliflower) and 0.54 (soybean). The production per plot that can be produced from K3 treatment was 2.01 kg/plot (5.03 tons/ha) of cauliflower and 0.43 kg/plot (1.08 tons/ha) of soybean.Keywords : Intercropping, Planting proportion, Cauliflower, Soybean